2014
DOI: 10.1007/s11240-014-0698-7
|View full text |Cite
|
Sign up to set email alerts
|

The StDREB1 transcription factor is involved in oxidative stress response and enhances tolerance to salt stress

Abstract: We have shown previously that the potato dehydration responsive element binding (StDREB1) transcription factor plays an important role in regulating and improving salt and drought stress-response genes in potato plant. To further characterize StDREB1 involvement in stress response, we focuse here on the investigation of the StDREB1 target genes by an Electrophoretic mobility shift assay. The data obtains indicated that the StDREB1 protein can bind to both GCC and DRE boxes in the promoter sequence of target ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 60 publications
(67 reference statements)
2
13
0
Order By: Relevance
“…This hypothesis was confirmed in a previous study indicating that the StDREB1 protein can bind to both the GCC and DRE boxes in the promoter sequence of target genes (Bouaziz et al 2015). Moreover, the StDREB1 transgenic potato plants showed improved resistance to F. solani infection (Charfeddine et al 2015a, b).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…This hypothesis was confirmed in a previous study indicating that the StDREB1 protein can bind to both the GCC and DRE boxes in the promoter sequence of target genes (Bouaziz et al 2015). Moreover, the StDREB1 transgenic potato plants showed improved resistance to F. solani infection (Charfeddine et al 2015a, b).…”
Section: Discussionsupporting
confidence: 66%
“…Recently, we have shown that StDREB1 plays an essential role in regulation of the oxidative stress response. The involvement of this transcription factor in the activation of osmoprotectant synthesis was also confirmed (Bouaziz et al 2015). These data showed that StDREB1 transcription factor plays an important role in promoting oxidative stress tolerance in potato.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The functional proteins belong to the first group and include the detoxification enzymes, membrane proteins, osmolytes biosynthesis enzymes, and proteins mediating macromolecules protection, while the second group includes the regulatory proteins such as proteinases, protein kinases, and transcription factors that regulate genes expression and signal transductions [ 8 , 29 ]. Many transcription factors have been identified and showed potential in enhancing plant tolerance to different harmful stresses through regulating the expression of the downstream stress-related genes [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Dehydration-responsive element binding (DREB) transcription factors belong to the AP2/ERF family and comprise DREB1 and DREB2 , which play a main role in regulating stress-tolerance pathways in plants [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%